Literature Review: Halal Culinary Marketing Strategy To Improve The Competitiveness MSMEs In Indonesia - Budi Utami; Eny Setyariningsih; M Syamsul Hidayat; Toto Heru DH (International Journal of Social Service and Research, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main pillars of the Indonesian economy, including the culinary sector. Food is considered one of the significant aspects that affect visitor satisfaction with a destination, especially Muslims. Local food that is currently trending is enough to increase its own interest in the community, especially Muslims, namely Warung Pecel based on Sharia or Halal. It is one type of MSME that combines the principles of shari'ah with their business activities. The purpose of this literature review is to identify marketing strategies that can be used to increase the competitiveness of Sharia pecel pinstripe rice stalls. This research uses the literature review method of journals from ScienceDirect, Researchgate, and Google Scholar. The results of the literature review show that there are 15 articles explaining several marketing strategies that can be applied to increase the competitiveness of Sharia pecel rice stalls. Relevant marketing strategies include the application of digital marketing, market segmentation, and appropriate targeting, branding and product differentiation, network marketing and strategic alliances, use of social media, value-based marketing, effective marketing promotion and communication, and experience marketing. In addition, by understanding the values of Sharia and promoting them effectively, Warung Pecel can differentiate itself from competitors and create a unique experience for customers. The limitation of the study which samples of MSMEs with pecel stalls.